Representation of Pelajar Rahmatan Lil Alamin Values in Non-Madrasah School through the Islamic Boarding School Curriculum - Habibah, Faticha Uhti; Hanafi, Muhammad; Munawwaroh (ICONELT, 2024)
This study examines the integration of the values of the Profil Pelajar Rahmatan lil Alamin (PPRA) in non-madrasah schools through the Islamic Boarding School Curriculum. The study of the Technical Guidelines for the Curriculum of Islamic Boarding Schools was used to find out whether the ten core values of PPRA are modesty, exemplary behavior, citizenship, equality, moderation, balance, justice, consultation, tolerance, and innovation. The findings show that the boarding school curriculum displays the implementation of PPRA. Teachers play an important role in realizing these values, thus increasing the development of students who are rahmatan lil alamin. However, empirical research is still needed to research the long-term of this curriculum. This paper contributes to developing the curriculum in Indonesia to see if PPRA can be applied to a broader scope outside of madrasas. The originality of the research lies in critical thinking through how PPRA can be applied in non-madrasah.